Tributes of Hawaiian tradition: the Pali and Battle of Nuuanu; Kaliuwaa Falls and Kamapuaa, the demigod (revised from the Hawaiian annual and Hawaiian folk-tales) - Thrum, Thomas G. (Thomas George), 1843-1932. (Honolulu, 1920)
Three tales about scenes of Oahu revised from the Hawaiian Annual and Hawaiian Folk-Tales.
The Pali and Battle of Nuuanu -- Kaliuwaa Falls and Kamapuaa the demi-god -- Kaliuwaa Falls or Sacred Valley.
Mode of access: Internet.
Keywords: Folklore -- Hawaii; Battles -- Hawaii -- Oahu; Legends -- Hawaii -- Oahu; Kaliuwaa Falls, Oahu